A review of the current knowledge and challenges of hydrothermal carbonization for biomass conversion. Issue 6 (December 2019) - Heidari, Mohammad; Dutta, Animesh; Acharya, Bishnu; Mahmud, Shohel
Abstract: Greenhouse gases emitted from the excessive use of fossil fuels are threatening the environment, and thus alternative resources like biomass are being considered as a replacement. Biomass with high moisture content is better treated by hydrothermal carbonization method than any other process to generate biofuel. Research on this method on a lab scale has progressed recently. However, due to the complex reaction mechanisms and operational barriers, more improvements are required to make it a commercial technology. This paper aims to review the development of hydrothermal carbonization with a focus on the practical aspects of the process. Many references have been reviewed critically to provide a well-structured source for improving this process. After providing information about the biomass structure and general knowledge of hydrothermal carbonization, the challenges faced in attempts to improve the process have been identified as lack of valid kinetic and heat transfer models and insufficient data on continuous and large-scale reactors. Useful and practical suggestions have been presented to tackle all these challenges. Highlights: Hydrothermal carbonization (HTC) should be industrialized to valorize wet biomass. Effect of operational parameters should be studied in both lab and industrial-scale. Kinetic and energy modeling are more challenging due to unknown chemical reactions. The approaches to address the gaps have been clearly explained. Combining HTC with other processes has been proposed.